12 weeks of kindergarten-based yoga practice increases visual attention, visual-motor precision and decreases behavior of inattention and hyperactivity in 5-year-old children - Jarraya, Sana; Wagner, Matthias; Jarraya, Mohamed; Engel, Florian (Frontiers in psychology, 2019)
The present study assesses the impact of Kindergarten-based yoga on cognitive performance, visual-motor coordination and behavior of inattention and hyperactivity in 5-year-old children. In this randomized controlled trial, 45 children (28 female; 17 male; 5.2±0.4 yrs) participated. Over 12 weeks 15 children performed Hatha-yoga twice a week for 30 minutes, another 15 children performed generic physical education (PE) twice a week for 30 minutes, and 15 children performed no kind of physical activities, serving as control group (CG). Prior to (T0) and after twelve-weeks (T1), all participants completed Visual Attention and Visuomotor Precision subtests of Neuropsychological Evaluation Battery and teachers evaluated children’s behavior of inattention and hyperactivity with the ADHD Rating Scale-IV. At T0, no significant differences between groups appeared. Repeated measures analysis of variance revealed that following Bonferroni-Holm corrections yoga, in comparison to PE and CG, had a significant positive impact on the development on behavior of inattention and hyperactivity. Further, yoga has a significant positive impact on completion times in two visumotor precision tasks in comparison to PE. Finally, results indicate a significant positive effect of yoga on visual attention scores in comparison to control group. 12 weeks of Kindergarten-based yoga improves selected visual attention and visual-motor precision parameters and decreases behavior of inattention and hyperactivity in 5-year-old children. Consequently, yoga represents a sufficient and cost-benefit effective exercise which could enhance cognitive and behavioral factors relevant for learning and academic achievement among young children.
Gesehen am 21.08.2019